2019
DOI: 10.1108/hff-12-2018-0744
|View full text |Cite
|
Sign up to set email alerts
|

Temperature distribution analysis in a fully wet moving radial porous fin by finite element method

Abstract: Purpose This paper aims to study the temperature performance with natural convection and radiation effect on a porous fin in fully wet condition. Design/methodology/approach The finite element method (FEM) is applied to generate numerical solution of the obtained non-dimensional ordinary differential equation containing highly nonlinear terms. The parameters which impact on the heat transfer of fin have been scrutinized by means of plotted graphs. Findings The porous fin is taken for the analysis in radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Khani et al (2016) using the spectral collocation method improved the totally wetted radial porous fin with radiation and natural convection. The finite element method have been utilised by Gireesha et al (2019) to Thermal performance of fully wet porous fin study the moving fin of radial profile under the totally wet condition. Their study showed that the fully wet nature of the porous fin provides better cooling performance compared to non-wetted porous fin.…”
Section: 4mentioning
confidence: 99%
“…Khani et al (2016) using the spectral collocation method improved the totally wetted radial porous fin with radiation and natural convection. The finite element method have been utilised by Gireesha et al (2019) to Thermal performance of fully wet porous fin study the moving fin of radial profile under the totally wet condition. Their study showed that the fully wet nature of the porous fin provides better cooling performance compared to non-wetted porous fin.…”
Section: 4mentioning
confidence: 99%
“…Khani et al 17 through the spectral collocation method studied the simultaneous variation of convection and radiation in a radial fin in completely wet condition. Gireesha et al 18 have carried out a study on a radial profiled moving porous fin under totally wet conditions. They determined that wet conditions around the fin intensifies the heat dissipation rate.…”
Section: Introductionmentioning
confidence: 99%
“…The refrigerator efficiency of fully wet fin has been conducted by Hatami et al 17 Both mass and heat transfer phenomena in a circular fin have been discussed by Hatami and Ganji. 18 The totally wet circumstance in pin fin has been analytically analysed by Vahabzadeh et al, 19 whereas the analysis in longitudinal fin is carried out by Darvishi et al 20 The finite element method has been implemented by Gireesha et al 21 to study the wet porous fin under radial profile moving with constant velocity.…”
Section: Introductionmentioning
confidence: 99%